Probabilitas Pelaksanaan Hak Angket Terhadap Pemilihan Umum di Indonesia - Nuranida Hasanah; Wicipto Setiadi (Jurnal USM Law Review)
This study aims to analyze the role of the right of inquiry in the Parliament's oversight function juridically and the probability of using the right of inquiry in elections in Indonesia. The demand for stronger election oversight can be seen from the survey results, which stated that 62.2% of respondents agreed to use the right of inquiry to investigate allegations of election fraud. However, the House of Representatives' right of inquiry proposal has generated pros and cons from various circles. The existence of several shortcomings in the regulation of the right of inquiry has the potential to cause legal uncertainty and new legal problems. Therefore, research is needed to determine the juridical position of the right of inquiry and the probability of its use in future elections. This normative law research uses statutory and conceptual approaches. Based on the research conducted, it is known that based on their duties and authorities, the independent institutions of KPU and Bawaslu are included in the executive branch of power so that they are not immune from the right of inquiry of the House of Representatives. The right of inquiry for elections can be exercised by improving the regulation of the right of inquiry to be more specific. Investigations in the right of inquiry include constitutional actions whose results are in the form of proposals regarding the formulation of policies regarding elections (both forming and improving laws) or as one of the supporting materials in the evidence of election disputes at the Constitutional Court. This study focuses on the probability of Parliament using its authority to conduct investigations in elections in Indonesia and its use in the constitutional system.